Flood risk assessment for Mulde River catchment transferring data from an observed meteorological flood event - Betul Aslantas; Verena Maleska; Laura V. Alvarez; Sherifdeen Olamilekan Babalola (Results in Engineering)
Extreme floods can cause significant damage to infrastructure, property, and human life and have long-lasting social, economic, and environmental impacts. Flood risk assessment is critical in areas where the frequency of flood events is altering due to climate change, anthropogenic warming, land use changes. Since the primary goal of flood risk management is to reduce the risk to a tolerable level, the risk assessment based on hydrological, hydrodynamic modeling, and damage analysis is essential to identify areas that are at risk of flooding, assessing the vulnerability of assets in the area, and evaluating the potential impacts on the human life, economy, and environment. The purpose of this study is developing a transferred approach between similar catchments to observe how the catchment response in terms of discharge and damage based on a particular extreme flood event in the past. To conduct the research, the meteorological variables from the Ahr River valley extreme flood event are acquired, and an approach is developed to transfer the same dataset into the Mulde River catchment to observe consequences of the event.